Musculoskeletal Problems in Fishermen Workers to Improve Community Economy in Bahuluang Village, Kep. Selayar, South Sulawesi - Miftakhul Nur Ilmi; Suryo Saputra Perdana; Dwi Rossela Komalasari (Engagement: Jurnal Pengabdian Kepada Masyarakat, 2023)
The purpose of this community service program is to minimize musculoskeletal problems in fishing workers in order to improve the economy of the community in Bahuluang Village. Bahuluang village has musculoskeletal problems that are quite high in the review of the data at the Lowa Health Center, this occurs due to ergonomic deficiencies when working as a fisherman in terms of measurement REBA (Rapid Entire Body Assessment) which results obtained a medium level of 7 subjects, High Level 6 subjects and very high risk 6 subjects. Also reviewed from interviews and specific examinations with the results of all fishing workers, namely 20 subjects complained of back pain with a diagnosis of lumbar physiotherapy Type 1 there are 10 subjects, lumbar type 2 there are 5 subjects, lumbar type 3 there are 2 subjects, and Sups. HNP (Hernia Nucleus Pulposus) there are 3 subjects. Complaints and problems were followed up with counseling related to the correct ergonomic position at work, stretching before work, and the first treatment at the time of injury with the PRICE method. The evaluation obtained after completing community service, there was a decrease in REBA (Rapid Entire Body assessment) scores of 9 subjects could be ignored and 11 subjects with low scores and from the results of interviews and specific examinations complaints of back problems have been reduced. In addition, some fishermen have started to work with normal hours of 7 hours in 6 days and have a positive impact, namely increasing the economic income of the Bahuluang community.